EVALUASI PENCAPAIAN TARGET KEGIATAN VAKSINASI COVID-19 DI KABUPATEN ROKAN HILIR TAHUN 2021 - Ahmad; Hetty Ismainar; Ahmad Hanafi (Jurnal Ners Indonesia, 2023)
COVID-19 vaccination is one of the Indonesian government's efforts to create herd immunity to deal with the COVID-19 pandemic. According to government regulations, COVID-19 vaccination coverage in Rokan Hilir Regency, Riau province has not yet reached the 100% target. This research aims to determine the description of COVID-19 vaccination activities in Rokan Hilir Regency in 2022. This research was qualitative research with a case study design. The sampling technique uses purposive sampling. There were 6 informants in this study, namely one head of disease prevention and control, one head of the surveillance and immunization section of the Rokan Hilir District Health Service, two heads of Community Health Centers, and two community members who were willing or unwilling to be injected with the vaccine. The research instrument used observation sheets and in-depth interview guidelines. Data analysis uses data triangulation. Results: In general, the problem mapping is in accordance with existing policies. In preparing the work plan, first look at priority areas, namely the many targets. In implementing the COVID-19 vaccination, the vaccination team has worked according to the SOPs and policies that have been issued by the regional government. At the monitoring and evaluation stage of vaccine distribution, both division heads and section heads have monitored and evaluated to see that the government program has been implemented with various acceleration efforts and that the vaccines have been distributed well, although not all on time Conclusion: In distribution, you must always ensure that the vaccine is still at a cold temperature during preparation, it is best for recording and reporting to involve the Office of population